Inter-commodity Price Transmission between Maize and Wheat in South Africa - Ramoroka, Philly; Muchopa, Chiedza L. (International Journal of Economics and Financial Issues, 2022)
The relevance of price transmission studies has grown in momentum in the Sub-Saharan Africa region over the last few decades especially in relation to grains that are also linked through food supply chains. Such studies give clear and insightful information into markets particularly the supply side and led to a better understanding of how sustainable supply chains can be delivered in the wake of climate change impacts. Hence, the study aimed at investigating inter-commodity producer price transmission between maize and wheat in South Africa. The study employed secondary time series data that covered a sample size of 29 years (1990 – 2018). Graphical trends revealed that prices of both commodities followed an upward trend although fluctuations were observed in specific periods. Granger causality tests were performed and revealed no bidirectional causality relationship between maize and wheat producer prices. However, unidirectional causality was found from maize to wheat prices. The significance of these findings is in their capacity to inform and bridge the knowledge gap in identifying patterns which can be used in interpreting price trends in maize and wheat markets (across commodities). The development of effective policies to improve marketing performance is important for sustainable supply of food.